BODY COMPOSITION OF BALI CATTLE HEIFER FED DIFFERENT PROTEIN AND ENERGY CONTENT OF DIET - Rahman, Abdur; Suarna, I W.; Suryani, N. N. (Jurnal Peternakan Tropika, 2017)
This research was conducted at sobangan animal husbandry research station for 3 months, using 12 calves with body neight range 102,50 ± 4,41kg. Ration given and teses were analyzed. At the nutrition and feed laboratory of Animal Husbandry Faculty, Udayana University. Data obtained was analysed using a raudomized block design with 4 tretments and 3 replicates. Those treatment consisted of 4 rations contain different level of protein and energi ratio as follows 12% PK  and 2000 ME kcal/kg (A), 13% PK and 2100 ME kcal/kg (B), 14% PK and 2200 ME  kcal/kg (C), 15% PK and 2300 ME kcal/kg (D). Variablel observed includins body water contet, body fat, body protein and fat reteution. This study resulted in that the four dara meters observed were statistically not defferent (P>0,05) for all treatments.It can be conduted that the increased of protein and energi  rations from 12% crude protein and 2000 ME kcal to 15% CP and 2300 ME kcal/kg gave no effect on body composition and fat retention on calves. However, the higher the crude protein and energi ration, the nigher fat retentioin on the body. Keywords: Balinese cattle, body composition, fat retention.